CONCERNING OR ACTING? THE DICHOTOMY BETWEEN DISCOURSE AND PRACTICE IN SUSTAINABLE CONSUMER BEHAVIOR OF PORTO ALEGRE’S CITIZEN DOI - 10.5752/P.1984-6606.2015v15n40p57 - Bossle, Marilia Bonzanini; Nascimento, Luís Felipe Machado do; Figueiró, Paola Schmitt; Trevisan, Marcelo; Muller, Hugo Fridolino (Revista Economia & Gestão, 2015)
The purpose of this paper is to identify the relationship between attitudes and environmentalbehavior among residents in the city of Porto Alegre in southern Brazil, using a Survey thatwas applied with 1200 citizens. We analyzed the descriptive statistics and conducted anANOVA to test the effects of demographic factors in a series of variables. The gap between“attitude” and “behavior” was confirmed. The willingness to pay a premium for products withenvironmental appeal, although present in all levels, is higher for people from higher incomeand educational backgrounds and is higher for cosmetics than for natural foods. Respondentsconsider environmental criteria at purchase and they know how to dispose of products.Consumers lack of a systemic view of the production and consumption chain. Although ourfindings have practical (to improve concern in the population) and academic (to compare withsimilar studies) implications, results cannot be generalized, because they are specificallyrelated to a single city. The results will be valuable in guiding business strategies, publicpolicy and further research. Consumers realize the importance of sustainable issues but theyneed further knowledge to put their awareness into practice. This paper jointly analyzesawareness, behavior, the importance of the environmental appeal of products andenvironmental problems. People tend to answer positively, but they fail to act accordingly.